2014
DOI: 10.1007/s00429-014-0935-1
|View full text |Cite
|
Sign up to set email alerts
|

The ascending median raphe projections are mainly glutamatergic in the mouse forebrain

Abstract: The median raphe region (MRR) is thought to be serotonergic and plays an important role in the regulation of many cognitive functions. In the hippocampus (HIPP), the MRR exerts a fast excitatory control, partially through glutamatergic transmission, on a subpopulation of GABAergic interneurons that are key regulators of local network activity. However, not all receptors of this connection in the HIPP and in synapses established by MRR in other brain areas are known. Using combined anterograde tracing and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 51 publications
8
54
0
Order By: Relevance
“…The MHb is connected to the MRN directly and indirectly via the IPN (Contestabile et al, 1987; Groenewegen et al, 1986; Herkenham and Nauta, 1979; Ogawa et al, 2014). The downstream connectivity of the MHb leading to a potential modulation of the MRN strongly suggests its role in regulating cognitive and emotional behaviors (Deakin, 2013; Herkenham and Nauta, 1979; Hsu et al, 2014; Ogawa et al, 2014; Szonyi et al, 2014; Varga et al, 2009). A recent study implicated the dMHb in the regulation of fear behavior (Yamaguchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MHb is connected to the MRN directly and indirectly via the IPN (Contestabile et al, 1987; Groenewegen et al, 1986; Herkenham and Nauta, 1979; Ogawa et al, 2014). The downstream connectivity of the MHb leading to a potential modulation of the MRN strongly suggests its role in regulating cognitive and emotional behaviors (Deakin, 2013; Herkenham and Nauta, 1979; Hsu et al, 2014; Ogawa et al, 2014; Szonyi et al, 2014; Varga et al, 2009). A recent study implicated the dMHb in the regulation of fear behavior (Yamaguchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a strong IPN output to the median raphe nucleus (MRN), recent data suggests that the MRN receives direct input from the MHb (Herkenham and Nauta, 1979; Ogawa et al, 2014). Therefore, the MHb could play a key role in an MRN-mediated modulation of other brain areas, particularly the hippocampus and the medial prefrontal cortex (Szonyi et al, 2014; Varga et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we extensively tested the rabbit anti-VGLUT3 antibody in experiments using VGLUT3 knock out animals (Szőnyi et al 2014). Immunostaining of VGLUT3 in raphe neurons was also tested by others (Mintz and Scott 2006; Shutoh et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Serotonergic neurons desynchronize the hippocampal activity and disrupt rhythmic discharge of septal cholinergic and GABAergic neurons (Assaf and Miller 1978; Kinney et al 1996; Vertes and Kocsis 1997). VGLUT3 containing glutamatergic neurons suppress the hippocampal ripple activity and disrupt memory consolidation (Wang et al 2015), and both of these cells can innervate more forebrain areas simultaneously (Szőnyi et al 2014). Although serotonergic and glutamatergic neurons are frequently investigated, it is unknown how many of them possess both transmitters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serotonergic nuclei also host glutamatergic mechanisms [6, 7], which are implicated in brain plasticity as well [8, 9]. In fact, earlier studies showed that the median raphe region (MRR) rather than the dorsal raphe (DRN) have a role in this process.…”
Section: Introductionmentioning
confidence: 99%